دراسة فعالية رفع قاع الجيب الفكي بطريقة البالون ومدى نجاحها - الياس, جول; المدلل, ياسر (Latakia University Journal -Medical Sciences Series, 2013)
هدف البحث إلى تقييم مقدار الزيادة في ارتفاع العظم عند رفع الجيب الفكي بطريقة البالون ومقارنته مع ارتفاع العظم الناتج عن باقي طرق رفع قاع الجيب الفكي, وتم استخدام تقنية البالون في رفع الجيب الفكي على 30 حالة رفع جيب فكي عند 27 مريضاً لديهم درد علوي خلفي أكثر من سنين وبحاجة لإجراء عملية رفع جيب فكي من أجل الزرع (ثخانة العظم المتبقي أقل من 5 ملم) تتراوح أعمارهم بين ( 27 – 55 سنة ) بمتوسط عمر 48 سنة, مع استثناء الأمراض العامة أو الموضعية وعدم وجود حمل أو إرضاع عند الإناث, وغياب مضادات الاستطباب الأخرى لرفع الجيب الفكي, وقد تم إجراء العمل في قسم جراحة الفم والفكين في كلية طب الأسنان بجامعة دمشق وتم متابعة المرضى في 5 فترات زمنية بعد العمل الجراحي بالصور الشعاعية بطريقة التصوير السني المخروطي (بعد العمل مباشرة, بعد 3 شهور, بعد 6 أشهر, بعد 9 أشهر, بعد سنة واحدة ) ومقارنة النتائج مع نتائج باقي طرق رفع قاع الجيب الفكي, ومن أهم النتائج التي توصل إليها البحث إلى وجود فروق دالة إحصائياً عند مستوى الثقة 95 % ( R = 5 % ) حيث تبين وجود زيادة في مقدار ارتفاع العظم بعد رفع الجيب الفكي بالبالون وبلغت نسبة النجاح 96,7 % بعد 6 أشهر و93,3 % بعد سنة واحدة, وتوصل البحث إلى عدد من المقترحات، أهمها: إن طريقة رفع الجيب الفكي بالبالون طريقة آمنة وفعالة وقليلة الاختلاطات ونسبة نجاح رفع الجيب الفكي بالبالون أعلى من نسبة نجاح باقي طرق رفع قاع الجيب الفكي عدا طريقة المدك العظمي المدعوم بالألياف البصرية الضوئية . The research aims to Evaluate bone thickness when sinus floor is elevated with balloon and compare it with bone thickness when the other techniques of sinus floor elevation are applied. The balloon technique of sinus floor lifting is applied on 30 sinus lifting cases in 27 patients who have more than 2 teeth dental loose in posterior superior area and need sinus lifting for dental implantation in this area ( thickness of bone less than 5 mm ) at an age of 27- 55 years old at average of 48 years old. We exclude patients with general and local diseases and pregnancy. The work had been done in the oral and jaws surgery department in the Faculty of dentistry at Damascus University and patients had been followed up in 5 periods using dental cone beam radiography (after the surgery, after 3 months, after 6 months, after 9 months, after 1 year ) and the results have been compared with the results of the other sinus floor lifting techniques. The most important findings of the research are: there are statistic variations at confidence level of 95 % ( R= 5 % ) which obtained increase in bone thickness after sinus floor elevation with balloon with a success rate of ( 96,7 % ) after 6 months and (93,3 %) after 1 year. The research found a number of recommendations and proposals, including that of the balloon technique in sinus lifting being a safe and active method with little complications and at rate of success more than other techniques of sinus floor elevation except the osteotome technique supported with fiber optic.